Genome-wide identification and expression analysis of MADS-box transcription factors reveal their involvement in sex determination of hardy rubber tree (Eucommia ulmoides oliv.) - Zhang, Xianzhi; Wang, Xinyi; Pan, Linsi; Guo, Wei; Li, Yongquan; Wang, Wencai (Frontiers in Genetics, 2023)
Eucommia ulmoides is a famous rubber-producing and medicinal tree species that produces unisexual flowers on separate individuals from the earliest stage of stamen/pistil primordium formation. To explore the genetic regulation pathway of sex in E. ulmoides, comprehensive genome-wide analyses of MADS-box transcription factors were performed for the first time in this work. A total of 66 non-redundant E. ulmoides MADS-box (EuMADS) genes were identified, they were classified into Type I (M-type, 17 genes) and Type II (MIKC, 49 genes). Complex protein-motif composition, exon-intron structure and phytohormone-response cis-elements were detected in MIKC-EuMADS genes, indicative of their highly diverse and key biological functions. Further tissue- and sex-specific transcriptome comparisons revealed 24 differentially-expressed EuMADS genes (DEGs) between male and female flowers, and two DEGs between male and female leaves. Quantitative real-time PCR (qRT-PCR) validation of 14 floral organ ABCDE model-related genes showed 6 male-biased A/B/C/E-class genes, 5 female-biased A/D/E-class genes and 3 non-biased A/E-class genes. In particular, one B-class gene EuMADS39 (ortholog of AtAP3) and one A-class gene EuMADS65 (ortholog of AtFUL) were both almost exclusively expressed in male trees, no matter in flower or leaf tissues. Collectively, these results suggested a critical role of MADS-box transcription factors in sex determination of E. ulmoides, which will contribute to decoding the molecular regulation mechanism of sex in this dioecious species.